Dexamethasone prevents hearing loss by restoring glucocorticoid receptor expression in the guinea pig cochlea. (6th May 2015) - Heinrich, Ulf‐Rüdiger; Strieth, Sebastian; Schmidtmann, Irene; Stauber, Roland; Helling, Kai
Abstract : Objectives/Hypothesis: Dexamethasone is widely used in the treatment of various inner ear diseases. However, knowledge about its direct impact on glucocorticoid receptor (GR) expression is still limited. Study Design: Prospective animal study in male guinea pigs. Methods: A therapeutic concentration of dexamethasone (8mg/mL) or a physiological concentration of NaCl (0.9% solution) were intratympanically injected into the ears of guinea pigs (n = 10 in each case) 14 hours prior to 90 dB noise exposure (1 hour). Eighteen ears were exposed to noise only. Seven untreated ears were used as controls. Auditory brainstem responses were recorded prior to noise exposure or treatment and 2 hours thereafter. The cochleae were removed from the bullae, transferred to fixative, and embedded in paraffin. GR expression was identified immunohistochemically in the cochlea. Local staining intensities were quantified for seven regions by a computer. Results: Dexamethasone application significantly lowered noise‐induced hearing loss. Statistically significant alterations in the average GR expression levels were identified exclusively in the spiral ligament. Comparing GR expression at the level of individual ear, numerous highly significant local associations were identified in the other six cochlear regions. Conclusions: The intratympanic application of dexamethasone is suitable for supporting cochlear homeostasis under stress conditions. The lateral wall, mainly responsible for potassium recycling, seems to be the main target in glucocorticoid therapy. Level of Evidence: NA Laryngoscope, 126:E29–E34, 2016